2020
DOI: 10.1136/vr.105818
|View full text |Cite
|
Sign up to set email alerts
|

Clinical reasoning in canine cervical hyperaesthesia: which presenting features are important?

Abstract: BackgroundTo evaluate whether clinical features from the history, presentation, physical and neurological examination of dogs with cervical hyperaesthesia are statistically predictive of the underlying diagnosis.MethodsTwo hundred and ninety-eight dogs presenting with cervical hyperaesthesia between January 2010 and October 2018 were investigated. Only neurologically normal dogs with cervical hyperaesthesia on examination were included, while those with concurrent neurological deficits including gait abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…A German study showed a sex predisposition for male individuals ( 46 ), but other studies do not show significant difference in sex distribution of this disease ( 47 , 48 ). The assembly of signalment, clinical signs, and laboratory findings of CSF and blood analysis associated with a quick clinical improvement after application of immunosuppressive therapy with glucocorticosteroids and an exclusion of an infectious etiology lead to the antemortem diagnosis of SRMA ( 40 , 48 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…A German study showed a sex predisposition for male individuals ( 46 ), but other studies do not show significant difference in sex distribution of this disease ( 47 , 48 ). The assembly of signalment, clinical signs, and laboratory findings of CSF and blood analysis associated with a quick clinical improvement after application of immunosuppressive therapy with glucocorticosteroids and an exclusion of an infectious etiology lead to the antemortem diagnosis of SRMA ( 40 , 48 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some diseases are traditionally associated with a poor outcome like neoplasia, protein-losing nephropathy or liver dysfunction. [1][2][3] In our case, corticosteroid administration as treatment of immune-mediated polyarthritis was assumed to be responsible for the thrombotic phenomenon. Even though cervical pain was marked and dilatation of venous structures was judged severe based on CT images, outcome remained excellent.…”
Section: Discussionmentioning
confidence: 76%
“…In canine patients affected by venous thrombosis, prognosis is strongly dependent on the primary condition promoting hypercoagulability. Some diseases are traditionally associated with a poor outcome like neoplasia, protein‐losing nephropathy or liver dysfunction 1–3 . In our case, corticosteroid administration as treatment of immune‐mediated polyarthritis was assumed to be responsible for the thrombotic phenomenon.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The first three basic cases deal with the neurological examination, a scheme for reflecting upon differential diagnoses (VITAMIN D scheme) (21) and the 5-finger rule for Clinical Reasoning (24). In several studies evaluating the 5-finger rule (onset, clinical course, symmetry of clinical signs, pain and neurological localization) and signalment for Clinical Reasoning specific patterns were identified to help in diagnosing and differentiating neurological diseases in dogs or cats (see Figure 1) (22,23,(25)(26)(27)(28). Furthermore 35 patient cases on the most frequently occurring diseases of the central and peripheral nervous system as well as myopathies could be created.…”
Section: Case Preparationmentioning
confidence: 99%